Is The Dorsal Dartos Flap Rotation Technique Successful in Children with Isolated Penile Torsion? - Yalçın, Kenan; Fırat, Fatih (Urology Journal, 2025)
Objective: Penile torsion is a counterclockwise rotational anomaly of the penile shaft or glans. We aimed to evaluate the results of dorsal dartos flap rotation technique in children with isolated penile torsion. Materials and Methods: 5470 boys who applied to our clinic between 2012 and 2022 for circumcision were evaluated for congenital isolated penile torsion. They were classified according to the degree and direction of torsion and clinical findings were analyzed. According to the degree of torsion, penile degloving or dorsal dartos flap rotation technique with circumcision was performed. Patients whose torsion corrected after penile degloving were excluded from the study. The results of dorsal dartos flap rotation technique were evaluated. Results: Congenital isolated penile torsion ≥60° was identified in 1.04 % (n=57) of the children. Eight patients whose torsion corrected after penile degloving were excluded from the study. 49 patients who underwent dorsal dartos flap rotation had a mean age of 4.94 years (1-9) and a mean operation time of 29.9 min (20-40). The mean degree of torsion was 77.6° (60-110). The mean operation times in the < 90° and ≥ 90° dorsal dartos flap groups were statistically significant (p<0.05). Residual torsion was statistically significant in the < 90° and ≥ 90° dorsal dartos flap groups (p<0.05). At the postoperative 1st and 6th month follow-ups, torsion less than 10 degrees was observed in 3 patients who underwent dorsal dartos flap rotation technique. No residual torsion was observed in other patients. Conclusion: Isolated penile torsion cases should not be overlooked during circumcision. It seems possible to obtain successful results with dorsal dartos flap rotation in moderate and severe torsions.